Enhancing the hydrophobicity of mangrove bark by esterification for oil adsorption - Asadpour, R. (IWA Publishing, 2014)
Oil spills generally cause worldwide concern due to their detrimental effects on the environment and the economy. An assortment of commercial systems has been developed to control these spills, including the use of agricultural wastes as sorbents. This work deals with raw and modified mangrove barks (Rhizophora apiculata), an industrial lignocellulosic waste, as a low cost adsorbent for oil-product-spill cleanup in the aquatic environment. Mangrove bark was modified using fatty acids (oleic acid and palmitic acid) to improve its adsorption capacity. The oil sorption capacity of the modified bark was studied and compared with that of the raw bark. Kinetic tests were conducted with a series of contact times. The influence of particle size, oil dosage, pH and temperature on oil sorption capacity was investigated. The results showed that oleic acid treated bark has a higher sorption capacity (2,860.00Â±2.00 mg/g) than untreated bark for Tapis crude oil. A correlation between surface functional groups, morphology and surface area of the adsorbent was studied by Fourier transform infrared spectrum, field emission scanning electron microscopy images and Brunauer-Emmett-Teller analysis. Isotherm study was conducted using the Langmuir and Freundlich isotherm models. The result showed that adsorption of crude oil on treated mangrove bark could be best described by the Langmuir model. Â© IWA Publishing 2014.